Women As Dominant Activator Of Creative Economy Based On Digital Market - Rudi Pranata (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
Nowadays, women have successfully shone with their existence. Their intelligence and expertise can no longer be underestimated because they have contributed to development. This study aims to describe the existence of women in the digital-based creative economy, especially in the use of the Shopee marketplace in the live feature. The results show there are 25 live Shopee accounts which dominated by woman. It can be inferred women competencies can upgrade the economic resources for the population or society as a whole.